Fast and accurate determination of sites along the FUT2 in vitro transcript that are accessible to antisense oligonucleotides by application of secondary structure predictions and RNase H in combination with MALDI-TOF mass spectrometry - Gabler, Angelika (Oxford University Press, 2003)
Alteration of gene expression by use of antisense oligonucleotides has considerable potential for therapeutic purposes and scientific studies. Although applied for almost 25 years, this technique is still associated with difficulties in finding antisense-effective regions along the target mRNA. This is mainly due to strong secondary structures preventing binding of antisense oligonucleotides and RNase H, playing a major role in antisense-mediated degradation of the mRNA. These difficulties make empirical testing of a large number of sequences complementary to various sites in the target mRNA a very lengthy and troublesome procedure. To overcome this problem, more recent strategies to find efficient antisense sites are based on secondary structure prediction and RNase H-dependent mechanisms. We were the first who directly combined these two strategies; antisense oligonucleotides complementary to predicted unpaired target mRNA regions were designed and hybridized to the corresponding RNAs. Incubation with RNase H led to cleavage of the RNA at the respective hybridization sites. Analysis of the RNA fragments by matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometry, which has not been used in this context before, allowed exact determination of the cleavage site. Thus the technique described here is very promising when searching for effective antisense sites.